If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n(n + 3) = 2n + 1 Reorder the terms: n(3 + n) = 2n + 1 (3 * n + n * n) = 2n + 1 (3n + n2) = 2n + 1 Reorder the terms: 3n + n2 = 1 + 2n Solving 3n + n2 = 1 + 2n Solving for variable 'n'. Reorder the terms: -1 + 3n + -2n + n2 = 1 + 2n + -1 + -2n Combine like terms: 3n + -2n = 1n -1 + 1n + n2 = 1 + 2n + -1 + -2n Reorder the terms: -1 + 1n + n2 = 1 + -1 + 2n + -2n Combine like terms: 1 + -1 = 0 -1 + 1n + n2 = 0 + 2n + -2n -1 + 1n + n2 = 2n + -2n Combine like terms: 2n + -2n = 0 -1 + 1n + n2 = 0 Begin completing the square. Move the constant term to the right: Add '1' to each side of the equation. -1 + 1n + 1 + n2 = 0 + 1 Reorder the terms: -1 + 1 + 1n + n2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 1n + n2 = 0 + 1 1n + n2 = 0 + 1 Combine like terms: 0 + 1 = 1 1n + n2 = 1 The n term is 1n. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. n + 0.25 + n2 = 1 + 0.25 Reorder the terms: 0.25 + n + n2 = 1 + 0.25 Combine like terms: 1 + 0.25 = 1.25 0.25 + n + n2 = 1.25 Factor a perfect square on the left side: (n + 0.5)(n + 0.5) = 1.25 Calculate the square root of the right side: 1.118033989 Break this problem into two subproblems by setting (n + 0.5) equal to 1.118033989 and -1.118033989.Subproblem 1
n + 0.5 = 1.118033989 Simplifying n + 0.5 = 1.118033989 Reorder the terms: 0.5 + n = 1.118033989 Solving 0.5 + n = 1.118033989 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + n = 1.118033989 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + n = 1.118033989 + -0.5 n = 1.118033989 + -0.5 Combine like terms: 1.118033989 + -0.5 = 0.618033989 n = 0.618033989 Simplifying n = 0.618033989Subproblem 2
n + 0.5 = -1.118033989 Simplifying n + 0.5 = -1.118033989 Reorder the terms: 0.5 + n = -1.118033989 Solving 0.5 + n = -1.118033989 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + n = -1.118033989 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + n = -1.118033989 + -0.5 n = -1.118033989 + -0.5 Combine like terms: -1.118033989 + -0.5 = -1.618033989 n = -1.618033989 Simplifying n = -1.618033989Solution
The solution to the problem is based on the solutions from the subproblems. n = {0.618033989, -1.618033989}
| 3/2(3x+3)=2(1-3x)+13 | | 3x+22=3+6x-5 | | 4(5+x)=20 | | 7(a+b)=7a | | 3(2x+9)=6x | | 90z+10z=100 | | 5a+10a=20 | | 1y+1=x | | 2x^3-x^2-20x+10=0 | | 10x+13=6x+113 | | 66-3x=15x+22 | | x*x+3=28 | | 97-3x=33x+17 | | 18P-0= | | 134-10x=9x+18 | | 4x=36+3x | | -66.66y=22 | | 22=15x | | 25-5= | | -0.003x^2+0.577x+2=0 | | 67x-45y=56x+8y | | 6x^2-19x=14 | | 219-5x=31x+19 | | m^2-10m+18=0 | | 9+-8x=32+-15x | | 11x-19=6x+11 | | 2-(6-2x)=0 | | 12x-15y=80 | | 2x^4-9*x^3-4x^2-5x=0 | | x*3+x^2-8*x-8=0 | | 7y-5=3x+23 | | 4(x+1)-3(x-3)=25 |